Potensi Ekstrak Etanol Rimpang Jeringau (Acorus calamus L.) Sebagai Spasmolitik - Marihot Pasaribu; Nataniel Tandirogang; Sjarif Ismail; Swandari Paramita; Agustina Rahayu Magdaleni; Hary Nugroho (Jurnal Sains dan Kesehatan, 2017)
Pain due to smooth muscle stiffness can occur in various circumstances of patients, ranging from normal circumstances such as menstrual pain, to a pathological condition of gastrointestinal infections. To overcome the pain it can be given medication to reduce muscle stiffness as spasmolytics, but there are side effects of the drug. Thus, the need for developing new spasmolytics drugs based on medicinal herbs with fewer side effects. This study was conducted to examine the potential of rhizome extract of jeringau (Acorus calamus L.) that is traditionally used by Dayak tribe to heal upset stomach. Spasmolytic activity of plant extracts tested with isolates organ methods of guinea pig ileum induced by histamine. Result of the study showed 0.3 mg/ml A. calamus rhizomes extract could decrease ileum contraction better than papaverine 0.03 mg/ml (p=0.00). The conclusion of this study is rhizome extract of jeringau (A. calamus) has the potential to be used as spasmolytics in treatment of health problems caused by smooth muscle contraction